Kajian Normatif Terhadap Legalitas Dan Implikasi Hukum Praktik Thrifting Sebagai Perdagangan Barang Bekas Di Indonesia - Anugrah, Jorian; Irzal Fardiansyah, Ahmad; Berdian Tamza, Fristia (Magister Kenotariatan, Universitas Jambi, 2026)
The phenomenon of used clothing trade or thrifting has emerged as an alternative economic trend in Indonesia, especially among urban youth. This practice raises legal concerns since most of the traded goods are imported used clothes prohibited under Indonesian positive law. This study employs a normative juridical approach using qualitative analysis of laws and regulations governing import and trade activities. The findings indicate that thrifting involving imported used clothing constitutes a violation of Minister of Trade Regulation No. 40 of 2022 and Law No. 7 of 2014 on Trade, as well as breaches consumer protection principles under Law No. 8 of 1999. The legal implications extend beyond economic crime to affect domestic textile industries and public health. Strengthening regulations and coordinated supervision is necessary to ensure that thrifting operates within a legitimate and equitable legal framework.